2022
DOI: 10.7150/jca.69617
|View full text |Cite
|
Sign up to set email alerts
|

CAV2 Regulates Mir-4723/Wnt7A Signalling Axis through Endocytosis and Epithelial-Mesenchymal Transition to Promote Proliferation, Invasion, and Metastasis of Pancreatic Cancer Cells

Abstract: Background: Pancreatic cancer is one of the most aggressive malignancies globally, with no improvement in the cure rates yet.Caveolin-2 (CAV2) has been repeatedly reported to play an important role in cellular transport and signalling and in exhibiting a pro-oncogenic response in a variety of tumours, although its specific action mechanisms in pancreatic cancer are not well documented. MiRNA is recognized as a therapeutic target for a variety of tumours, making it an important regulator of the Wnt/β-catenin si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Additionally, our analysis revealed that polymorphism of IGF2BP2 gene that is differentially expressed in carcinoma of FOM [ 35 ] was found to be associated with less favorable oral cancer clinical characteristics [ 36 ]. DLGAP4 and COL4A6 that were found to be differentially expressed in carcinoma of anterior 2/3 of the tongue were found to be associated with poor overall survival in cancer, and the COL4A family was discovered to be a major component of the basement membrane (BM) that has recently been found to be involved in tumor angiogenesis and progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our analysis revealed that polymorphism of IGF2BP2 gene that is differentially expressed in carcinoma of FOM [ 35 ] was found to be associated with less favorable oral cancer clinical characteristics [ 36 ]. DLGAP4 and COL4A6 that were found to be differentially expressed in carcinoma of anterior 2/3 of the tongue were found to be associated with poor overall survival in cancer, and the COL4A family was discovered to be a major component of the basement membrane (BM) that has recently been found to be involved in tumor angiogenesis and progression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When expressed in cells, miR-155 inhibits endogenous praja2 accumulation and prevents ligand-induced endocytosis of EGFR. The role of other miRNAs in the endocytic trafficking and RTK turnover as well as their impact on cancer cell growth and metastasis have been previously reported 67 69 . However, to our knowledge, our work provides the first demonstration of the existence of a signaling circuitry that mechanistically links oncogenic miRNAs to the ubiquitin pathway and RTK turnover.…”
Section: Discussionmentioning
confidence: 95%